(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: Describe the current situation of depression, anxiety, and stress in students of specialization level I at Hanoi Medical University in 2022 and associated factors. Research subjects and methods: Cross-sectional descriptive study on 308 students of Specialization level I at Hanoi Medical University in 2022 selected for the study by convenience sampling method, using the DASS-21 scale (depression, anxiety, stress scale). Analyze data using STATA software. Results: The rate of symptoms of depression, anxiety, and stress among students of specialization level I at Hanoi Medical University in 2022 is 37,01%; 39,61%; 27,60%. Factors related to symptoms of depression, anxiety, and stress of research subjects include marital status, frequent problems in relationships, chronic diseases, and pressure to study theory at school, clinical learning pressure, hospital duty and exam pressure, the relationships are statistically significant with p < 0.05. Conclusion: Students of specialization level I have to endure stress during my studies, leading to symptoms of anxiety, depression, and stress. Therefore, managers need to develop lists of key supports to help specialist students deal with issues of depression, anxiety and stress at medical facilities.